Adaptive and Constitutive Activations of Malic Enzymes Confer Liver Cancer Multilayered Protection Against Reactive Oxygen Species. Issue 2 (26th August 2021) - Lee, Derek; Zhang, Misty Shuo; Tsang, Felice Ho‐Ching; Bao, Macus Hao‐Ran; Xu, Iris Ming‐Jing; Lai, Robin Kit‐Ho; Chiu, David Kung‐Chun; Tse, Aki Pui‐Wah; Law, Cheuk‐Ting; Chan, Cerise Yuen‐Ki; Yuen, Vincent Wai‐Hin; Chui, Noreen Nog‐Qin; et al.
Abstract : Background and aims: HCC undergoes active metabolic reprogramming. Reactive oxygen species (ROS) are excessively generated in cancer cells and are neutralized by NADPH. Malic enzymes (MEs) are the less studied NADPH producers in cancer. Approach and Results: We found that ME1, but not ME3, was regulated by the typical oxidative stress response pathway mediated by kelch‐like ECH associated protein 1/nuclear factor erythroid 2‐related factor (NRF2). Surprisingly, ME3 was constitutively induced by superenhancers. Disruption of any ME regulatory pathways decelerated HCC progression and sensitized HCC to sorafenib. Therapeutically, simultaneous blockade of NRF2 and a superenhancer complex completely impeded HCC growth. We show that superenhancers allow cancer cells to counteract the intrinsically high level of ROS through constitutively activating ME3 expression. When HCC cells encounter further episodes of ROS insult, NRF2 allows cancer cells to adapt by transcriptionally activating ME1. Conclusions: Our study reveals the complementary regulatory mechanisms which control MEs and provide cancer cells multiple layers of defense against oxidative stress. Targeting both regulatory mechanisms represents a potential therapeutic approach for HCC treatment.